INFLUENCE OF A PROGRAM OF PHYSICAL ACTIVITY APPLY A CHILDREN SOROPOSITIVO (Fiep Bulletin - online, 2014)
The carrying the HIV virus have weakness in the system and cardiac muscle, and is more susceptible to the development of hypertension and constant loss of body mass. Currently there is sufficient information suggesting that the physical exercises are not deleterious for patients infected by HIV, and may, in contrast, provide physical and psychological benefits. Thus, the goal of this study was to analyze the influence of a program of regular physical activity on morphological variables and neuromuscular linked HIV positive children in the institution Casa Vhida located in the city of Manaus. They were referred to the program 11 children with 7.27 ± 1.84 years; 115 ± 0.12 cm and 22.17 ± 7.28 kg, and evaluated variables morphological and neuromuscular. All the children were subjected to a program of physical activity with 12 weeks in duration with two sessions per week. Each session had duration of 50 minutes, providing itself with three parts: a) 05 minutes of introduction with motor activities of elongation; B) 40 minutes of instruction and practice of motor activities and recreational activities in large groups and stations; C) 05 minutes of closure, with discussion of the activities carried out in order to return to calm, and all sessions applied by the same teacher. The treatment was so descriptive statistics using average and the standard deviation for all variables, and for the comparison between pre - and post-program was used to test samples for Student T-dependent, with the significance level of 0.05. The results show that the morphological variables and neuromuscular did not show significant differences between the two moments analyzed. Despite the lack of statistical differences changes when the observation of absolute values, which shows a positive response when the application of systematic physical activity in children HIV positive.
Keywords: HIV; physical activity; soropositivos